Biro Jodoh Online: Studi Aalisi Penggunaan Kaidah Dharar - Nurulia Shalehatun Nisa (Prodi HKI IAI Miftahul Ulum Pamekasan, 2023)
This research discusses the existence of a matchmaking agency using analysis of the rules of dharar (bad luck). There have been many recent phenomena related to online matchmaking agencies, namely a place to find a mate online or via electronic media using technology. Conceptually, this research is normative or library based, where this research conceptually examines the existence of online matchmaking agencies which are then analyzed in depth using traditional rules to show the novelty of this research. The results of this research show that the preference for online matchmaking agencies can be said to be a complementary tool in finding a life partner, meaning that under any circumstances the majority in looking for a partner prefer to use the services of their parents, siblings or friends. So this online matchmaking agency is not used as the main tool in finding a life partner, but as a complementary tool to open the gate to a more serious stage. If it is related to the theory of emergency rules, the use of online matchmaking agencies is not yet included in emergency conditions